2017
DOI: 10.1111/jphp.12738
|View full text |Cite
|
Sign up to set email alerts
|

Bis(phenylimidazoselenazolyl) diselenide elicits antinociceptive effect by modulating myeloperoxidase activity, NOx and NFkB levels in the collagen-induced arthritis mouse model

Abstract: The myeloperoxidase activity in paw and NOx and NFkB levels in spinal cord are related to antinociceptive properties of BPIS in CIA model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
(72 reference statements)
0
14
0
Order By: Relevance
“…The organochalcogen compounds present an atom of selenium, tellurium or sulfur in their chemical structure. They are promising pharmacological agents that have significant biological activities and may exhibit antiinflammatory, antioxidant, antinociceptive and neuroprotective properties (Chagas et al 2017, Quines et al 2014, Nogueira et al 2004). Therefore, organoselenium and organotellurium compounds are promising pharmacological agents known to have a wide range of biological effects (Nogueira et al 2004, Tiekink 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The organochalcogen compounds present an atom of selenium, tellurium or sulfur in their chemical structure. They are promising pharmacological agents that have significant biological activities and may exhibit antiinflammatory, antioxidant, antinociceptive and neuroprotective properties (Chagas et al 2017, Quines et al 2014, Nogueira et al 2004). Therefore, organoselenium and organotellurium compounds are promising pharmacological agents known to have a wide range of biological effects (Nogueira et al 2004, Tiekink 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Mice with CIA show shortened response latency to noxious heat radiation of fixed intensity to the hind paw [7, 18] and shortened latency to show licking of the hind paw or jumping behavior after placement on a hot plate of 52 °C [19]. The authors of these studies attributed these changes to inflammatory changes in the nociceptive neurons.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that sensitivity to the noxious thermal stimulation is increased in the RA models [7, 19, 37, 38], indicating that the nocifensive function of thermosensation (i.e., detection of contact with a noxious high temperature) is potentiated in mice with CIA. In this study, the plate with the temperature ranging from 43 to 49 °C (phase III in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal hyperalgesia was assessed using a hot plate test as described by the method of Chagasa et al (2017), with minor modifications. All the animals were placed into the Perspex cylinder of the hot plate (Ugo Saile, Italy) maintained at 55.0 ± 0.5°C, and time to discomfort reaction (licking paws or jumping) was recorded as response latency.…”
Section: Methodsmentioning
confidence: 99%